Performance of MPSO-MPPT on PV-Based DC Microgrid in Partial Shading Conditions - Haneef Nouval Alannibras Humaidi; Mokhammad Isnaeni Bambang Setyonegoro; Sarjiya Sarjiya (IJITEE (International Journal of Information Technology and Electrical Engineering), 2021)
Microgrid is a controllable decentralized group of energy resources and loads with the ability to operate both in grid-connected or island modes. Photovoltaic (PV) is one of the sources that are commonly used in microgrid. PV has a good ability to convert solar irradiation into electrical energy, especially under ideal condition, namely uniform irradiation or non-shading condition. However, PV often has some problems when facing partial shading condition. In this condition, PV does not produce optimal power because it stucks at the local maximum power point (MPP), thus it unables to track the global MPP. For this reason, it is necessary to implement a smart maximum power point tracker (MPPT) that can solve this problem. Furthermore, MPPT will be implemented in pulse width modulation (PWM) to control the buck converter. This study is focused on designing a laboratory scaled microgrid system with PV sources and controlled by modified particle swarm optimization (MPSO)-based MPPT. The 360 Wp PV array used consisted of two strings of three series modules Solarex MSX-60. The performance of the proposed method was compared with perturb and observe (P&O)-based MPPT, which was the commonly used method on MPPT. Furthermore, it was found that P&O and MPSO performed relatively similar accuracy (with difference of 0.04%) in non-shading condition. However, in partial shading condition, MPSO could perform better by producing greater output power so that it delivers better accuracy (98.74% to 99.11%) compared to P&O (57.95% to 71.87%). However, MPSO required a slightly longer time to converge because it had more complicated method and more computational load.